Microinjection quality control in zebrafish model for genetic manipulations - Doua Abdelrahman (17280667) (2021)
Microinjection technique is one of the essential methodologies that are used widely in zebrafish research. Microinjection is utilized to perform genetic manipulations within the developing zebrafish model. Further, this technique is used to study a wide range of genetic diseases and gene of interest role in early developmental processes. Thus, quality control for microinjection is an essential factor to ensure experimental reproducibility and consistency. In this technical note, in vitro transcribed synthetic mRNA encoding green fluorescence protein (eGFP), and red fluorescent protein (m-cherry) as well as fluorescein and rhodamine fluorescent dyes were injected into a single-cell zebrafish embryo for volume quality control. Given the importance of having quality control system and methodology to yield similar genetic manipulation within the zebrafish embryo: We aimed to establish the unified delivery of injected material into zebrafish one cell stage embryo. We aimed to establish consistency of the injected volume into mineral oil droplets that will serve as a quality control parameter to conforms a quality control practice to ensure the reproducibility of the microinjection technique. The calibration of microinjection droplet size resulted in the visualization of fluorescent protein and dyes in the zebrafish embryo with precise volumes of delivered materials under the control of needle opening, injection pressure and time. Other Information Published in: MethodsX License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.mex.2021.101418